Prevention of posterior capsule opacification in experimental studies - Łukaszewska-Smyk, Agnieszka; Kałużny, Józef (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The pharmaceuticals inhibiting proliferation of epithelium cells or causing their death were tested in experimental studies on PCO prevention. The following antymetabolites were tested: 5-fluorouracil, dounomycin, methotrexat and colchicine, epithelial antibodies against epithelial cells, toxins, hyperosmolar agents and heparin, indomethacine and lignocaine. Moreover, gene therapy with the use of apoptose genes was applied. None of the attempts to prevent PCO was useful for effective and safe clinical treatment.